The Effect of Audit Fee, Audit Rotation, and Auditor Reputation on Audit Quality (Empirical Study on Manufacturing Companies Listed on the Idx for the Period 2014-2018) - Nursiam, N; Febry Krisna Putri; Pardi, P (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this research is to examine the effect of audit fees, audit rotation, and auditor reputation on audit quality. The population in this study is manufacturing companies listed on the IDX period 2014-2018. The total sample of research is 345 companies determined by purposive sampling. Data analysis was done by logistic regression and SPSS Statistic 20. The result of this study shows that audit fee does not affect audit quality, while audit rotation and auditor reputation have a significant effect on audit quality.